Study on the Detection Characteristics and Response Mechanism of SnS2-Based Sensors for SO2 and SOF2 - Chengjun Li; Mengyang He; Shuangshuang Tian; Jiawei Yuan; Jincong Wang; Yi Li (Chemosensors, 2022)
Based on the wide application of sulfur hexafluoride (SF6) gas in the power industry, the analysis and detection of its decomposition components have become important technical means for state detection and fault evaluation of gas-insulated equipment. The gas-sensitive characteristics and adsorption mechanism of the SnS2 sensor for SO2 and SOF2 gases were investigated using SO2 and SOF2, the main SF6 decomposition components, as the target detection gases. SnS2 gas-sensitive materials and components were prepared, and the temperature response, concentration response, response recovery and stability of the SnS2 sensor for the two SF6 decomposition components were tested based on the gas-sensitive test platform. The results demonstrate that the sensor had the best working performance at 200 °C, with obvious response and ideal recovery for both target gases and good stability in a certain time. Based on the first principle, the SnS2 surface structure model and the target gas adsorption model were established, and the adsorption mechanism was analyzed in terms of frontier molecular orbital theory to verify the correctness of the gas-sensitive test results. The gas-sensitive test analysis and simulation calculation can provide data basis and theoretical support for the study of SF6 decomposition components detected by gas sensors.